Sughd Writing - Shoira Amriddinovna Indiaminova (Genius Journals, 2023)
This article describes the culture of the Sogdian script, its origins, the regions where the Sogdian script was found, and the historiography of the Sogdian script. The Sogdian inscriptions found in the Mug Castle were of great importance in the study of the history of ancient Sogdiana. The inscriptions on the ambassador's clothes in the Varhuman Palace in Afrosiyab provide valuable information about the political life of Sogdiana in the VIIVIII centuries. Samples of Sogdian inscriptions have been found in many parts of Asia and Europe, which proves how widespread this inscription is. The reason why Sogdian writing is so widespread is that language and writing were the main means of communication on the Great Silk Road. At the same time, the question of why the Sogdian inscriptions were lost was also touched upon.
Keywords: Sughd; Sogdian inscription; ancient letters; Mevancha